Unlocking the black box between TQM practices and organisational performance through learning capability and market orientation: insight from Pakistan's textile sector. (4th March 2022) - Mahmood, Shahid; Khan, Kanwal Iqbal; Abdin, Syed Zain Ul; Ahmad, Mumtaz
The enduring debate to resolve the intricacy between total quality management elements and performance is yet to be concluded. Relying on the resource-based view of the firm, the current study addresses this issue by adding organisation learning capability and market orientation as contingent factors between total quality management practices and performance. The data was collected from the managers of 270 textile firms through questionnaires. The results reveal that parallel mediation of both organisational learning capability and market orientation is fully supported. The current study extends the total quality management research and contributes by providing a new mechanism between the total quality management and organisational performance. These novel findings provide new dimensions for policymakers to consider motivational factors (learning orientation and market orientation) along with total quality management elements for elevating the performance of their organisations.